Construction-Induced Vibrations And Green Concrete: Literature Review And Case History - William M. Camp (Deep Foundations Institute, 2010)
Construction-induced earthborn vibrations have long been recognized as a potential problem with respect to the constructed environment and various vibration criteria are in use to prevent damage. A special case of construction vibration control is the protection of early-age or ?green? concrete. Unlike limits for damage prevention to building stock, there is no rational, widely accepted limit for protection of early-age concrete. Numerous criteria have been proposed or reported in the literature and the most relevant and rational proposals are summarized herein. These findings are applied to a case history involving both bored and driven piles. Vibration measurements were made during pile driving activities and the vibration magnitude was evaluated with respect to the exposure of freshly-placed and curing concrete to the earthborn vibrations. The maximum vibration magnitude at the applicable distances from pile driving was on the order of 0.3 inches per second. Based on the most persuasive literature, threshold values of 0.8 inches per second or even 1 to 2 inches per second for the protection of green concrete appear to be well-supported. Consequently, it was concluded that the pile driving activities and bored pile construction could proceed simultaneously.